Overexpression of DGKI in Gastric Cancer Predicts Poor Prognosis - Huang, Chao; Zhao, Jiefeng; Luo, Chen; Zhu, Zhengming (Frontiers in Medicine, 2020)
Background: Diacylglycerol kinase iota (DGKI) is overexpressed in a variety of cancers and is associated with poor prognosis in colon cancer. This study evaluated the prognostic value of DGKI in gastric cancer (GC) using data from The Cancer Genome Atlas (TCGA). Methods: RNA sequencing results and clinical data of gastric adenoma and adenocarcinoma samples were obtained from the TCGA database (https://portal.gdc.cancer.gov). The Wilcoxon or Kruskal-Wallis test and logistic regression were used to analyze the relationship between DGKI and the clinicopathological characteristics of GC patients. Univariate Cox regression and Kaplan-Meier analysis were used to analyze the clinicopathological characteristics of GC patients and the relationship between DGKI and overall survival time, and multivariate Cox regression analysis was used to identify independent risk factors affecting the prognosis of GC patients. Gene set enrichment analysis (GSEA) was performed using the TCGA dataset. Results: DGKI was overexpressed in gastric tumors and was related to poor prognosis (p = 0.003). Overexpression of DGKI in GC was significantly correlated with high grade (OR=1.71 for G3 vs. G2), stage (OR = 2.08 for II vs. I) and T classification (OR = 4.64 for T4 vs. T1; OR = 3.99 for T3 vs. T1; OR = 3.37 for T2 vs. T1) (all p-values < 0.05). DGKI (OR = 7.34; p = 0.000) was an independent risk factor affecting the survival of GC patients. The MAPK signaling pathway was differentially enriched with DGKI overexpression. Conclusion: DGKI overexpression may be a potential molecular marker for poor prognosis in GC. The MAPK signaling pathway may be one of the key pathways related to DGKI regulation in GC.